Comparative study of the elastic properties of adamantane and 1-chloroadamantane at high pressure and different temperatures and at order–disorder transitions. Issue 3 (15th January 2021) - Gromnitskaya, Elena L.; Danilov, Igor V.; Brazhkin, Vadim V.
Abstract : The disorder–order phase transition is easily detected by jumps in the volume and velocities of ultrasound, while the bulk modulus B practically does not change. Abstract : We present a comparative ultrasonic study of the elastic properties of adamantane and 1-chloroadamantane at high pressure (up to 1.4 GPa) and different temperatures (77–293 K) and at order–disorder transitions. The ultrasonic method provides complementary pictures of the order–disorder transitions in diamondoids under pressure. The equation of state of adamantane and 1-chloroadamantane was determined up to 1.4 GPa from ultrasonic measurements of bulk modulus and is in good accordance with the previous equations developed from volumetric data. We measured the bulk and shear moduli and Poisson's ratio of adamantane and 1-chloroadamantane up to 1.4 GPa. The behaviors of elastic moduli are different for adamantane and 1-chloroadamantane. This indicates that the substitution of one hydrogen atom for chlorine significantly reduces both elastic moduli, particularly the shear modulus (≈30%). Although the pressure dependences of the bulk modulus B are almost linear and its pressure derivatives for adamantane and 1-chloroadamantane are close to each other ( B ′ ≈ 10–12), a jump is hardly observed on the pressure dependence B ( P ) for adamantane at the transition from the plastic to ordered phase, whereas the pressure dependence of the bulk modulus for 1-chloroadamantane exhibits a jump of almost 17%. The experimental dependences of the bulk modulus and relative changes in the volume for both materials clearly demonstrate that the compressibility of 1-chloroadamantane is much higher for both phases. The Poisson coefficient calculated from our experimental data is larger for 1-chloroadamantane, having lower both bulk and shear moduli.